Improving EFL non-English majors’ pronunciation via a flipped classroom: A modular approach - Xin Zhang; Asmaa AlSaqqaf (International Journal of Instruction, 2025)
Despite common pronunciation challenges faced by Chinese non-English majors, research on incorporating technology-enhanced language learning within a flipped classroom framework to improve their English pronunciation remains scarce. This study aimed to explore the effectiveness of a flipped classroom module in enhancing the English pronunciation of this demographic group. A quasiexperimental design under the quantitative approach was employed, involving 100 undergraduate students divided into an experimental group with 49 students and a control group with 51 students. The experimental group received 14 weeks of teaching utilizing a flipped classroom module, which included pre-recorded pronunciation lessons for self-study before class and in-class interactive activities such as pronunciation drills. Meanwhile, the control group received the same duration of English pronunciation instruction but through traditional methods, consisting mainly of lectures and minimal practice. Independent samples t-tests and paired samples t-tests were employed to determine any significant differences between the two groups based on the pre-and post-test results evaluating English pronunciation. Results showed that the experimental group demonstrated a significantly higher improvement in English pronunciation after the intervention, with a significant level of 0.008 and a large effect size of 1.043. The study concludes that integrating technology into the flipped classroom model can significantly improve language skills, particularly pronunciation, among EFL learners.